From Digitized to Dialogic Writing: How ICT Literacy Shapes Intertextual Competence in Cyber-Learning Environments - Edy Waloyo; Rudi Hartono; Sri Wahyuni; Henrikus Joko Yulianto (Universitas Pendidikan Ganesha, 2025)
This study investigates how ICT literacy influences intertextual competence in digital academic writing. It aims to analyze students’ ability to evaluate, synthesize, and dialogically integrate digital sources in a cyber-learning environment. Employing an explanatory sequential mixed-methods approach, the research collected quantitative data from structured surveys, analyzed using descriptive statistics, and qualitative data from interviews, open-ended questionnaires, and students writing samples, examined through thematic analysis. Findings indicate that while students demonstrate strong ICT skills in accessing and organizing digital information, many face difficulties in critically synthesizing texts, constructing coherent arguments, and positioning themselves epistemically. Sources are often used for citation rather that for constructing meaning. However, when instructional scaffolds such as source-mapping and contrastive reading are applied, students begin to show enhances intertextual awareness. The study concludes that ICT literacy alone does not ensure dialogic academic writing. Instead, writing instruction must incorporate critical, culturally responsive, and dialogic pedagogies to foster intertextual competence. These findings have implication for digital curriculum design and academic writing instruction in online higher education.